Sustained mass coral bleaching (2016–2017) in Brazilian turbid-zone reefs: taxonomic, cross-shelf and habitat-related trends - Teixeira, Carolina D.; Leitão, Rodrigo L. L.; Ribeiro, Felipe V.; Moraes, Fernando C.; Neves, Leonardo M.; Bastos, Alex C.; Pereira-Filho, Guilherme H.; Kampel, Milton; Salomon, Paulo S.; Sá, João A.; Falsarella, Ludmilla N.; Amario, Michelle; et al. (Coral reefs, 2019)
Between 2014 and 2017, an unprecedented heat stress accumulated and propagated across the tropical oceans and resulted in the so-called Third Global Bleaching Event (TGBE). Information about the effects of the TGBE in marginal coral reef provinces are still scarce, but can be relevant to understand the trajectories of coral reefs as climate changes intensify. Akin to deep mesophotic reefs and reefs in thermally stressed regions, low diversity, turbid-zone reefs may exhibit high bleaching tolerance due to local adaptations and conditions (e.g., shading by turbidity). Here, we summarize previous bleaching events in the tropical Western South Atlantic Ocean and explore taxonomic, cross-shelf and habitat-related bleaching trends in the Abrolhos reefs in February, May, June and October 2016, and March 2017. Fire corals ( Millepora spp.) were the most affected, but all scleractinian species and several octocorals and zoanthids also bleached. Bleaching prevalence was higher in shallow coastal and offshore reef arcs than in deeper mesophotic reefs. All coral species bleached, but there were taxonomic and habitat-related trends in bleaching prevalence. Several species bleached less in the sites and habitats where their abundance was lower. As of March 2017, coral mortality was overall low across the region (< 3% of total coral cover). Our results add to the recent evidence that deep reefs provide partial refugia for a few coral species, and that turbid-zone reefs may be less susceptible to climate stress due to shading, higher heterotrophy levels, and local adaptations.